Information, overconfidence and trading : do the sources of information matter? - Abreu, Margarida (2012)
We investigate how the strength of the positive association between frequency of trading and information acquisition is dependent on investors’ self‐confidence and on the sources of information used by investors. Our results confirm that the more frequently individual investors invest in information, the more they trade in financial products. Our results also confirm previous findings that overconfident investors, who show a better than average bias, trade more frequently. In this paper, we add to this literature by investigating if the strong and positive relationship between investment in information and intensity of trading in financial assets is sensitive to the sources of information used by investors, and if this influence is different for overconfident and non‐overconfident investors. We conclude that overconfident investors trade more frequently when they collect information directly using specialized sources and that nonoverconfident investors trade less frequently when they use professional advice from the bank/account manager.